Surface modification of hematite photoanodes with CeOx cocatalyst for improved photoelectrochemical water oxidation kinetics - Ahmed, Mahmoud Gamal (2020)
Hematite is a promising photoanode for solar water splitting by photoelectrochemical (PEC) cells, but its performance is limited by the slow kinetics of water oxidation reaction or oxygen evolution reaction (OER). Surface modification of hematite photoanodes with a suitable water oxidation cocatalyst is a key strategy for improving the kinetics of water oxidation. In this study, a CeOx overlayer is deposited on the surface of the hematite photoanode by a water‐based solution method with ceric ammonium nitrate (CAN) followed by heat treatment. The photocurrent of CeOx‐modified hematite is 3 times higher than that of pristine hematite (at 1.23 V vs. RHE) under AM 1.5G, 1 sun conditions. Through hole‐scavenger measurements, Tafel plot analysis, and electrochemical impedance spectroscopy, it is concluded that CeOx overlayer increases the hole injection efficiency, improves the surface catalytic activity, and enhances charge transfer across the photoanode/electrolyte interface. These observations are attributed to the synergistic effects of Ce3+/Ce4+ redox species in CeOx and the oxygen vacancies. This work elucidates the role of CeOx as an efficient cocatalyst overlayer to improve the OER kinetics of photoanodes.